Psycological foundations to integrate the emotion in formative assessment - Torres Lizarazo, David Fernando; Monsalve Flórez, Jhon Alexánder (Rastros Rostros, 2021)
This reflexive article has as objective the theoretical analysis of emotions within the processes of formativeassessment. To achieve this purpose, a documentary review is used, framed within the interpretive paradigm ofsocial science. In the first place, the relationship between Revee’s theory and formative evaluation is developed;this process is connected, in the second instance, with Heller’s theory of feelings. In conclusion, the dialoguebetween formative assessment and emotion is rebuilt, as a starting point for the constructivist relationshipamong the teacher, the student and the educational institution, whose purpose is that the student reachesautonomy for their learning process
Keywords: assessment; formative assessment; students; emotion